Two-dimensional cylinderical bioheat transfer through cloth-insulated human skin - Rouf Gulzar; Mir Aijaz; Javid Gani Dar; Ibrahim M. Almanjahie (Case Studies in Thermal Engineering)
Monitoring temperature profiles of in vivo tissues under harsh conditions is indeed an interesting problem but the problem becomes challenging when the body is covered by clothes. Accurate temperature tracking is crucial during various treatments like radiation therapy, medical examinations, occupational safety, sports performance analysis, etc. The paper investigates temperature variations in cloth-covered skin and subcutaneous tissue at unpleasant temperatures. In order to simulate the issue more accurately, a mathematical model based on the two-dimensional cylindrical bioheat equation along with appropriate initial and boundary conditions has been solved numerically. The temperature distribution in skin and subcutaneous tissue covered by cloth has been determined and the findings of the model were pictured graphically. The results were validated by comparing them with the published research on similar domain and objectives. The results of this study can be implemented to predict how much heat is distributed throughout the tissue and to identify the root causes of why patients undergoing thermal treatments like targeted tumour hyperthermia or cryosurgery might sustain burns or cold injuries.